Habits and the Anomalies in Intertemporal Choice - Wathieu, Luc (Management Science, 1997)
This paper analyzes a model of discounted utility under habit formation. Habit formation means that utility in each period is determined by the difference between the received outcome and the customary outcome at that point in time. Preferences are rational, in the sense that the decision maker correctly anticipates the habit formation process and behaves in a dynamically consistent manner, i.e., plans are truly carried out. The purpose is to demonstrate that this generalization of the discounted utility model accounts, jointly and in a meaningful way, for the most striking anomalies with respect to classical discounted utility theory. The common difference effect is explained first. This effect, also called decreasing impatience effect, has usually been viewed as evidence against exponential discounting. Then, the frequently observed preference for increasing sequences of outcomes is examined. Such preference, under the traditional discounted utility model, would be regarded as a paradoxical case of negative discounting. A discussion of the descriptive, prescriptive, and normative values of the model is included.